2009
DOI: 10.1080/10599240902779436
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Studies in Agricultural Populations: Observations and Future Directions

Abstract: This paper reviews epidemiologic studies of cancer among agricultural populations to identify possible associations and to provide a focus for future investigations. Meta-analyses of mortality surveys of farmers find excesses of several cancers, including connective tissue, non-Hodgkin lymphoma, Hodgkin disease, and multiple myeloma and cancers of the skin, stomach and brain and deficits for total mortality, heart disease, total cancer, and cancers of the esophagus, colon, lung and bladder. Meta-analyses of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 20 publications
6
96
4
3
Order By: Relevance
“…In addition, we did not take into account co-exposures to other chemicals, such as polybrominated diphenyl ethers (PBDEs) or phthalates, which may also be involved in the development of cancer. The relationship between the human exposure to other environmental pollutants and total cancer has been assessed in previous epidemiological studies (Blair and Freeman, 2009;Mink et al, 2012). We highlight the positive Spearman correlations observed between all POPs in our study; therefore, the associations found with single chemicals may be surrogates of exposure to other more toxic agents or even to mixtures of POPs with similar physicochemical characteristics (Arrebola et al, 2013b;Brauner et al, 2012b).…”
Section: Discussionsupporting
confidence: 66%
“…In addition, we did not take into account co-exposures to other chemicals, such as polybrominated diphenyl ethers (PBDEs) or phthalates, which may also be involved in the development of cancer. The relationship between the human exposure to other environmental pollutants and total cancer has been assessed in previous epidemiological studies (Blair and Freeman, 2009;Mink et al, 2012). We highlight the positive Spearman correlations observed between all POPs in our study; therefore, the associations found with single chemicals may be surrogates of exposure to other more toxic agents or even to mixtures of POPs with similar physicochemical characteristics (Arrebola et al, 2013b;Brauner et al, 2012b).…”
Section: Discussionsupporting
confidence: 66%
“…45 46 Chronic exposure among farm workers has been associated with numerous adult health problems, including respiratory problems, memory disorders, dermatologic conditions, depression, neurologic deficits including Parkinson disease, miscarriages, birth defects, and cancer. [47][48][49][50] Prenatal organophosphate pesticide exposure has been associated with adverse birth outcomes, such as decreased birth weight and length 51 and smaller head circumference. 52 A large prospective birth cohort study that measured pesticide exposure in pregnant farm workers in California and followed their offspring found lower mental development index scores at 24 months of age 53 and attentional problems at 3.5 and 5 years of age.…”
Section: Synthetic Chemical Exposure Pesticidesmentioning
confidence: 99%
“…This comparative approach is warranted because farm workers share three important similarities to firefighters around occupational disease. First, farm workers face a heightened risk of various kinds of cancers, including melanoma, non-Hodgkin's lymphoma, leukemia, and multiple myeloma as well as brain, cervical, esophageal, oral, prostate, and stomach cancers (Blair & Freeman, 2009;Blair & Zahm, 1995;Fincham, Hanson, & Berkel, 1992;Mills, Dodge, & Yang, 2009). Second, this heightened risk is likely the result of occupational exposures to pesticides, solvents, exhausts, dusts, and microbes.…”
Section: Firefighters Farm Workers and Occupational Cancermentioning
confidence: 99%